2009
DOI: 10.1016/j.jinorgbio.2008.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum X-ray absorption edges from 200 to 20,000eV: The benefits of soft X-ray spectroscopy for chemical speciation

Abstract: We have surveyed the chemical utility of the near-edge structure of molybdenum x-ray absorption edges from the hard x-ray K-edge at 20,000 eV down to the soft x-ray M 4,5 -edges at ~230 eV. We compared, for each edge, the spectra of two tetrahedral anions, MoO 4 and MoS 4 2-. We used three criteria for assessing near-edge structure of each edge: (i) the ratio of the observed chemical shift between MoO 4 2-and MoS 4 2-and the linewidth, (ii) the chemical information from analysis of the near-edge structure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 50 publications
2
37
0
1
Order By: Relevance
“…1) is attributed to dipolar 1s → 4d electronic transitions (Farges et al, 2006). Previous studies found that the enhanced pre‐edge feature is indicative of Mo=O bonds in the Mo tetrahedral configuration (George et al, 2009; Wichard et al, 2009). In this study, a similar pre‐edge feature can be found in the 20 mM Na 2 MoO 4 solution sample, indicating that the Mo coordination environment is predominantly tetrahedral under such reaction conditions (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…1) is attributed to dipolar 1s → 4d electronic transitions (Farges et al, 2006). Previous studies found that the enhanced pre‐edge feature is indicative of Mo=O bonds in the Mo tetrahedral configuration (George et al, 2009; Wichard et al, 2009). In this study, a similar pre‐edge feature can be found in the 20 mM Na 2 MoO 4 solution sample, indicating that the Mo coordination environment is predominantly tetrahedral under such reaction conditions (Fig.…”
Section: Resultsmentioning
confidence: 98%
“… Calculated 4c-DR-TDDFT (VDZ/aVDZ) XAS spectra near molybdenum M 4,5 -edges of MoS 4 2– using different xc functionals and their comparison with experimental results. 120 To ease comparison, the spectra were shifted so that the M 5 -line maxima are centered on the experimental value. (a) Theory and (b) experiment (reprinted from ref ( 120 ) with permission from Elsevier).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the degree of Mn complexation varies enormously with pH, highlighting the need to base hypotheses on a range of information. Soft X‐ray (L‐edge) absorption spectroscopy techniques, which are potentially more sensitive to the chemical environment around the absorbing ion, may also serve to better resolve the ligands binding foliar Mn (George et al. , 2009).…”
Section: Discussionmentioning
confidence: 99%